2020
DOI: 10.1007/s00167-020-05892-y
|View full text |Cite
|
Sign up to set email alerts
|

Patella-patellar tendon angle decreases in patients with infrapatellar fat pad syndrome and medial patellar plica syndrome

Abstract: Purpose Infrapatellar fat pad (IPFP) syndrome and medial patellar plica (MPP) syndrome are two recognized causes of anterior knee pain. However, diagnosing these syndromes is challenging without arthroscopic examination. The aim of this study was to evaluate sagittal patellar tilt in patients with IPFP syndrome or MPP syndrome by measuring the patella-patellar tendon angle (PPTA) in affected patients. Methods Eighty-three patients with anterior knee pain who underwent diagnostic arthroscopy that confirmed isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…In the present study, sagittal patellar tilt was evaluated in patients with MPP syndrome, chondromalacia patella, and IPFP syndrome by measuring PPTA. This study demonstrated that PPTA was significantly lower in patients with MPP syndrome, chondromalacia patella, and IPFP syndrome than in those of control group, which was consistent with the results of previous studies [ 3 , 4 ]. However, there was no significant difference in PPTA among the patients in each disease.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, sagittal patellar tilt was evaluated in patients with MPP syndrome, chondromalacia patella, and IPFP syndrome by measuring PPTA. This study demonstrated that PPTA was significantly lower in patients with MPP syndrome, chondromalacia patella, and IPFP syndrome than in those of control group, which was consistent with the results of previous studies [ 3 , 4 ]. However, there was no significant difference in PPTA among the patients in each disease.…”
Section: Discussionsupporting
confidence: 93%
“…The most known reasons of AKP are trauma and overuse [ 12 , 13 ], but MPP syndrome, chondromalacia patella, and IPFP syndrome are well-known conditions that could cause AKP [ 3 , 4 ]. The medial, lateral, superior and inferior synovial plicae are normal structures of the knee joint, but plica-related AKP is mostly caused by impingement of medial plica.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the IPFP in KOA patients was more like that of young, healthy people after manual release. Kim et al 23) reported that the patella-patellar tendon angle was smaller in patients with IPFP syndrome (137.3 ± 4.9° (± SD)) than in people without knee pathology (141.4 ± 2.9°) (p<0.001). Assuming that the control group has better knee function, we speculate that improving mobility of the IPFP in patients with KOA may help to achieve better knee function.…”
Section: Discussionmentioning
confidence: 98%